Factors influencing nurse fatigue during COVID-19: regression vs. fuzzy-set qualitative comparative analysis - Zhang, Huanyu; Liu, Zhixin; Liu, Junping; Feng, Yajie; Zou, Dandan; Zhao, Juan; Wang, Chen; Wang, Nan; Liu, Xinru; Wu, Lin; Liu, Zhaoyue; Liang, Libo; et al. (Frontiers in Public Health, 2023)
Nurses during COVID-19 who face significant stress and high infection risk are prone to fatigue, affecting their health and quality of patient care. A cross- sectional study of 270 nurses who went to epidemic area to support anti-epidemic was carried out via online survey during the COVID-19 pandemic on November 2021